2012
DOI: 10.1080/13648470.2011.646944
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the DSM‐IV Outline for Cultural Formulation on multidisciplinary case conferences in mental health

Abstract: The Diagnostic and Statistical Manual of Mental Disorders of the American Psychiatric Association (DSM-IV-TR) includes an Outline for Cultural Formulation (CF) that identifies cultural information that can be used to modify diagnosis, clinical assessment and treatment plan. This study examined the use of the CF by a Cultural Consultation Service in the psychiatric assessment of patients referred by primary care providers. The study uses conversation analysis of 12 clinical case conferences to explore the ways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In Montreal's CCS, the perceived utility of the OCF did not differ between clinicians and non-clinicians (e.g., culture brokers), though psychologists found it more useful than did physicians (Kirmayer, Thombs et al, 2008c). Dinh and colleagues (2012) showed that the OCF changed dynamics of a multidisciplinary group by increasing the participation of non-medical professionals who could contribute to understanding the patient's social world. Assigning this task of cultural assessment to specialized personnel may enhance the cultural information gathered, but deprive treating clinicians of interacting with the patient directly.…”
Section: Resultsmentioning
confidence: 99%
“…In Montreal's CCS, the perceived utility of the OCF did not differ between clinicians and non-clinicians (e.g., culture brokers), though psychologists found it more useful than did physicians (Kirmayer, Thombs et al, 2008c). Dinh and colleagues (2012) showed that the OCF changed dynamics of a multidisciplinary group by increasing the participation of non-medical professionals who could contribute to understanding the patient's social world. Assigning this task of cultural assessment to specialized personnel may enhance the cultural information gathered, but deprive treating clinicians of interacting with the patient directly.…”
Section: Resultsmentioning
confidence: 99%
“…Though slow to emerge, it is promising that research is evolving in this area (Dinh, Groleau, Kirmayer, Rodriguez, & Bibeau, 2012) and the challenges in its application, including a need for theory, is being recognized (Aggarwal, 2014). Undoubtedly, more research is needed to evaluate the effectiveness of applying cultural formulation as a tool to improve diagnosis and treatment, the findings of which would inform further development and modification in the utilization of this tool.…”
Section: The Cultural Formulationmentioning
confidence: 99%
“…13 As per Korner, our team model fits an interdisciplinary team model as we ‘meet regularly in order to discuss and collaboratively set treatment goals for the patients and jointly carry out the treatment plans’. 14 There is positive evidence for case conferencing 15 in mental health to improve interdisciplinary collaboration and knowledge transfer, and it is shown that utilising a case template 16 can improve medical care in other settings.…”
Section: Discussionmentioning
confidence: 99%